Financing of New SMEs in Latvia – Opportunities and Obstacles - Erika Pancenko; Marika Sakele (Copernican Journal of Finance & Accounting, 2024)
The relevance of the study is related to the fact that the predominant factor for the development of economic activity for newly established enterprises is the possibility of business financing. However, despite the availability of alternative sources of financing for new small and medium-sized enterprises (SMEs), there are various obstacles to obtaining them. The aim of the study is to analyse the opportunities for raising finance from various financial sources and the related obstacles for new SMEs in Latvia. The study used quantitative and qualitative methods of analysis, a survey of SME entrepreneurs, structured interviews with experts, data processing methods and the method of analysis and synthesis. This paper determines for what purpose and what financial sources entrepreneurs will use if necessary, as well as what obstacles exist to obtaining financing. The results of this study may be beneficial for both financial organizations that finance companies and new SMEs in the financial decision-making process.